RESPON PERTUMBUHAN DAN HASIL TANAM SAWI (Brassica juncea L) TERHADAP INTERAKSI BOKASHI SAMPAH PASAR DENGAN UREA - Andri Permata Timung; Benyamin Gaso; Mesak Y Awang (Politeknik Pertanian Negeri Kupang, 2021)
The aims of the study were to: determine the interaction effect of market waste bokashi fertilizer with urea dose on the growth and yield of mustard greens and determine the best dose of market waste bokashi fertilizer with various doses of urea to increase the growth and yield of mustard greens. This research was conducted using factorial RBD, namely: Factor I: P1: without bokashi; P2: 5 tons/ha; P3: 10 tons/ha; P4: 15 tons/ha, Factor II consists of Q1: No treatment; Q2: 100 kg/ha; Q3: 200 kg/ha. Data analysis using Anova and continued with LSD level 5%. The results showed that: 1) There was a single factor effect of various doses of market waste bokashi fertilizer and urea on the growth and yield of mustard greens; 2) Supply of the best market waste bokashi fertilizer with a dose of 15 tons/ha Bokashi and 20 g/m2 urea for mustard cultivation. Key Words: growth, market waste bokashi, mustard greens, urea, yield